Does Carbon Pricing Matter? Evidence from a Global Sample - Khalid S. Al-Abdulqader; Abdul-Jalil Ibrahim; JingKai Ong; Ahmed A. Khalifa (Energies)
Implementing a carbon pricing policy in any country remains a complex challenge, requiring the careful navigation of economic, social, and political factors to ensure policy coherence and stakeholder buy-in. Given the critical role of carbon pricing in achieving net-zero emissions by 2050, this study provides empirical evidence on the impact of carbon price implementation on carbon emission reductions globally. The study is motivated by the a priori assumption that carbon pricing policies incentivize polluters to adopt carbon-neutral technologies, leading to emission reductions. Using data from 30 jurisdictions between 1990 and 2020, comprising both developed economies and eight emerging markets where either a carbon tax, an emission trading system, or both have been implemented, we assess the effectiveness of carbon pricing mechanisms while controlling for economic growth, population, energy intensity, and environmental policy stringency. The findings confirm that carbon pricing leads to a significant reduction in emissions, with the Emission Trading System proving to be more effective in accelerating emission reductions than the carbon tax. Specifically, the Emission Trading System is associated with a 12.06% reduction in carbon emissions, compared to an 8.91% reduction under the carbon tax. These results underscore the importance of market-based mechanisms in driving decarbonization efforts. The findings also have critical policy implications, highlighting the need for tailored carbon pricing strategies that align with national economic structures and political contexts. Robustness checks and policy recommendations are provided to guide policymakers in designing effective carbon pricing frameworks to enhance climate mitigation efforts.